The juridification processes of the peasant round of Macusani - Arredondo Villar, Claudia (2021)
This paper explores the juridification processes that take place in the peasant rounds of the Macusani District in the Puno region, viewed as a place where legal pluralism operates at the margins of the State. For that purpose, elements of the state are identified in the practices and discourse of the peasants. Especially, the legal language adopted by this peasant organization and what that means for the construction of its legitimacy and authority. This qualitative research employs the ethnographic method to analyze a case documented during fieldwork, an emergency meeting of the peasant round of Macusani is narrated, in which several moments where legal instruments are strategically invoked by the peasants are identified. This adoption and appropriation of legal terms and instruments, such as the International Labor Organization’s 169 treaty, the Nº 27908 Law of Peasant rounds, the human rights discourse, and other state norms are employed in the arguments of the peasants about what is considered fair.